Peran Kualitas Pelayanan Dalam Meningkatkan Kepuasan Pelanggan Pada UMKM Eagle Decal - Trisfani, Amelia; Hersusetiyati, Hersusetiyati`; Aisyah, Nur; Audina, Septi (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2026)
This study aims to analyze the role of service quality in enhancing customer satisfaction at Eagle Decal SMEs located in Bandung Regency. This research uses a descriptive qualitative method with data collection through observation, interviews, and documentation involving owners, customer service staff, and several customers. The results of the study indicate that service quality dimensions such as reliability, empathy, and assurance have been applied quite well, while responsiveness remains the main weakness. Customer satisfaction tends to increase when services are delivered in a friendly and informative manner, but slow responses reduce customer loyalty. The conclusion highlights the importance of improving response speed and consistency in customer service. Training for staff and the development of standard operating procedures (SOP) are recommended as strategies to enhance service quality and strengthen customer loyalty.